Nghiên cứu tổng hợp các phức chất tạo bởi ion Co2+, Ni2+, Cu2+ và Zn2+ với amino axit–khảo sát tính kháng khuẩn - Huỳnh, Lê Văn; Xuân, Đinh Viết (Vietnam Journal of Chemistry, 2014)
Some transition metal ions in normal conditions are capable of complex with some organic ligands, creating complex is more rigid than 109 constant, the complex does not have catalytic activity, but they have antimicrobial properties and antifungal high. On the other hand there are complex constants durable 103 < Kb < 109 to have catalytic activity. These complexes have catalytic activity plays an important role in the production process, such as in trace analysis, use water treatment wastewater, industrial waste. This paper is the result of complex integrated study of some transition metal ions Co2+, Ni2+, Cu2+ and Zn2+ with glycyne. The research results are a scientific basis for complex applications in the technology process. Keywords: Synthesis of complexes, antifungal